Underutilized Native Biobío Berries: Opportunities for Foods and Trade - López, María D.; Baenas, Nieves; Retamal-Salgado, Jorge; Zapata, Nelson; Moreno, Diego A.
The Biobío Region in Chile presents special edaphoclimatic characteristics and biodiversity that make it suitable for the introduction and development of some berries that are understudied in terms of their health-promoting composition and characteristics. Chilean strawberry (Fragaria chiloensis ssp. chiloensis, form chiloensis) and calafate (Berberis microphylla G. Forst.) have been underused despite having interesting nutritive values and health-promoting capacities. The polyphenolic compositions of Chilean strawberry and calafate were characterized by HPLC-DAD-ESI-MSn analyses, as well as their antioxidant potential (in ORAC and DPPH assays). The major secondary metabolites present in Chilean strawberry and calafate were ellagic acid derivatives and anthocyanins, respectively, being the anthocyanins more closely related to the higher antioxidant capacity found in the berries. Therefore, the Biobío Region berries analyzed are rich in bioactive phytochemicals with health-promoting characteristics. This represents an opportunity for the food industry and for international trade with Chilean berries, as well as a potential way of promoting rural development in the region.